2013
DOI: 10.1108/cdi-09-2012-0084
|View full text |Cite
|
Sign up to set email alerts
|

Developmental networks at work: holding environments for leader development

Abstract: Purpose-The purpose of this paper is to elaborate how an adult development perspective can further the understanding of developmental networks as holding environments for developing leaders confronted with challenging experiences. Design/methodology/approach-The article utilizes constructive developmental theory (C-D theory) to explore and address the implications of an adult development lens for leader development, especially as they confront complex leadership challenges that trigger anxiety. Findings-Theore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 54 publications
0
19
0
2
Order By: Relevance
“…Here, we propose that mentors and other developers that comprise a diverse leader's developmental network—the group of people who take an active interest in and action to advance focal individuals' careers and personal growth (Higgins & Kram, )—can provide an array of career support (e.g., sponsorship, visibility, coaching, challenging assignments, role modeling) and psychosocial support functions (e.g., affirmation and confirmation, friendship, counseling, inspiration and motivation) (Cotton, Shen, & Livne‐Tarandach, ; Kram, ; Murphy & Kram, ), as well as holding behaviors (e.g., containment, empathetic acknowledgment, enabling perspective) (Ghosh, Haynes & Kram, ; Kahn, ; Ragins, Ehrhardt, Lyness, Murphy, & Capman, ) that can offset and mitigate the challenges that often prevent them from reaching the C‐suite and boards.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we propose that mentors and other developers that comprise a diverse leader's developmental network—the group of people who take an active interest in and action to advance focal individuals' careers and personal growth (Higgins & Kram, )—can provide an array of career support (e.g., sponsorship, visibility, coaching, challenging assignments, role modeling) and psychosocial support functions (e.g., affirmation and confirmation, friendship, counseling, inspiration and motivation) (Cotton, Shen, & Livne‐Tarandach, ; Kram, ; Murphy & Kram, ), as well as holding behaviors (e.g., containment, empathetic acknowledgment, enabling perspective) (Ghosh, Haynes & Kram, ; Kahn, ; Ragins, Ehrhardt, Lyness, Murphy, & Capman, ) that can offset and mitigate the challenges that often prevent them from reaching the C‐suite and boards.…”
Section: Introductionmentioning
confidence: 99%
“…A growing body of literature is suggesting ways in which workplace challenges and specific workplace-based interventions may be important in contributing to consciousness development (Ghosh et al 2013;Joiner and Josephs 2007;Palus and Drath 1995;Rooke and Torbert 2005;Torbert et al 2004;Valcea et al 2011). However, again, there has been very little empirical research that has tested this.…”
Section: Environmental Readiness Factorsmentioning
confidence: 97%
“…Since then, a growing body of academic research has shown associations between higher consciousness development and better leadership performance and organisational outcomes (Barker and Torbert 2011;Bartone et al 2007;Brown 2011;Harris and Kuhnert 2008;Helsing and Howell 2013;Joiner and Josephs 2007;Strang and Kuhnert 2009). There are also increasing calls for, and interest in, the design of interventions to promote adult consciousness development in business schools and in the leadership/executive development arena Bradbury-Huang 2011, 2014;Drago-Severson and Blum-DeStefano 2014;Ghosh et al 2013;Joiner and Josephs 2007;Kegan and Lahey 2009;Valcea et al 2011;Vincent et al 2013Vincent et al , 2014.…”
Section: Introductionmentioning
confidence: 97%
“…Defined as "the unfolding sequence of a person's work experiences over time" (Arthur, Hall, & Lawrence, 1989, p. 8), a career is personal, often focusing on paid employment yet extending beyond that to include any aspect of life that connects people and the societies in which they live. Given the associated pace of innovation and the demise of lifetime employment, the intelligent career framework focuses on empowering individuals to develop awareness of their identities and motivations to work, to see the workplace as an arena for developing skills and knowledge, and to understand how personal and professional contacts can support career decisions and enhance career development (Amundson, Parker, & Arthur, 2002;Ghosh, Haynes, & Kram, 2013;Parker, 2008). We use the term career to mean that everyone has a career and only one career, although that career may involve a variety of jobs, fields, and industries.…”
Section: Introductionmentioning
confidence: 99%